Lead and bismuth corrosion resistant w-containing multi-element max phase ceramic material and application thereof

CN123003290APending Publication Date: 2026-10-30NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611185229.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

有效解决了现有陶瓷材料在高温液态金属环境中的腐蚀溶解问题

Benefits of technology

(1)本发明是以Cr1.75Ti1.65Mo0.6AlC3为基体,利用W元素来取代等摩尔比例减少的Mo元素,制备掺杂W元素的Cr-Ti-Mo-W多元素MAX相陶瓷材料。W元素的引入具有双重作用机制:一方面,部分W占据4f晶格位置,通过增强过渡金属-碳键合强度提升MC型碳化物层的结构稳定性,同时削弱过渡金属与铝层的键合,使其更易断裂,从而促进Al的选择性溶出;另一方面,W的掺入有效降低了Al2O3形成的吉布斯自由能,有利于在贫氧条件下诱导生成致密的Al2O3保护层。得益于上述机制,所制备的陶瓷材料在铅铋腐蚀环境中表现出长达2000小时的稳定性,显著提升了其耐腐蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003290A_ABST
    Figure CN123003290A_ABST
Patent Text Reader

Abstract

The application discloses a W-containing multi-element MAX phase ceramic material resistant to lead and bismuth corrosion and application thereof. 1.75 Ti 1.65 Mo 0.6 AlC3 as a matrix, and is prepared by partially substituting Mo elements with W elements; the chemical formula is Cr 1.75 Ti 1.65 Mo 0.6 x W x AlC3, wherein 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of MAX phase ceramic materials technology, specifically a W-containing multi-element MAX phase ceramic material resistant to lead-bismuth corrosion and its applications. Background Technology

[0002] Nuclear power, as a highly efficient and clean energy source, boasts advantages such as high energy density, stable operation, and economic sustainability. Its power generation process does not produce greenhouse gases, its annual utilization hours consistently exceed 7000 hours, it is unaffected by weather, and its long-term operating costs are relatively low, making it a strategic choice for optimizing energy structure and addressing climate change. In fourth-generation nuclear power systems, the lead-cooled fast reactor (LFR) is one of the key reactor types under development. It uses liquid lead-bismuth alloy (LBE) as a coolant, which is considered an ideal coolant material due to its excellent neutron performance, strong resistance to radiation damage, good heat transfer, and low melting point and high boiling point. However, under high-temperature operation, LBE can corrode reactor structural components (such as the main pump impeller and fuel cladding). This corrosion involves complex physicochemical processes, including the dissolution of material components, erosion of the material by flowing LBE, migration of elements in the solid and liquid phases, and chemical reactions between corrosion products and impurities. These effects lead to material performance degradation, posing a threat to reactor operational safety. Therefore, solving the material corrosion problem is crucial for the development of lead-cooled fast reactor technology.

[0003] Currently, candidate structural materials for LFRs mainly include stainless steels such as T91 and 316L, as well as ceramic materials. While austenitic stainless steels, represented by 316L and 15-15Ti, possess excellent high-temperature creep resistance and radiation resistance, they are prone to elemental dissolution in high-temperature liquid lead-bismuth alloys (LBE), leading to strength loss. Although ceramic materials experience less mass loss, their intrinsic brittleness and susceptibility to surface crack propagation due to corrosion make them difficult to apply directly. Max phase ceramics, which combine the ductility and toughness of metals with the corrosion resistance of ceramics, are promising candidate materials due to their thin oxide layer after corrosion. Existing reports commonly include Ti-based max phase ceramics such as Ti3Al. 1-x Si x C2 ( x While Si doping of Al sites can suppress surface crack formation to some extent (=0~1), the resulting Ti-containing oxide layer remains relatively porous, making element dissolution difficult to prevent. Cr-Ti-based MAX phases, such as Cr2TiAlC2, developed in recent years, exhibit a certain degree of inhibition against element dissolution because some Ti is replaced by Cr, making it easier to form an oxide film under oxygen-deficient conditions. However, this modification strategy is still insufficient to guarantee the formation of a continuous and protective oxide layer, thus failing to fundamentally eliminate element dissolution and significantly improve the corrosion resistance of MAX phase ceramics in lead-bismuth environments. Summary of the Invention

[0004] To address the shortcomings of existing technologies and further improve the corrosion resistance of MAX phase ceramics in lead-bismuth environments, this invention provides a W-containing multi-element MAX phase ceramic material resistant to lead-bismuth corrosion. This effectively solves the corrosion and dissolution problem of existing ceramic materials in high-temperature liquid metal environments.

[0005] The present invention provides a lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material, with Cr as the main component. 1.75 Ti 1.65 Mo 0.6 The material was prepared using AlC3 as a matrix by partially substituting Mo with W; its chemical formula is: Cr 1.75 Ti 1.65 Mo 0.6 x W x AlC3, where 0 <x≤0.2。

[0006] The ceramic material can be made by the following two methods: Method 1: Step (1): Using Cr powder, Ti powder, Mo powder, W powder, Al powder, and C powder as raw materials, place them in a ball mill jar for ball milling to ensure that the powders of each element are mixed evenly. Intermittent ball milling is used to prevent the powders from sticking together due to excessive temperature.

[0007] Step (2): The uniformly mixed powder is loaded into a graphite mold and placed in a high-temperature tube furnace. A high-temperature solid-state reaction is carried out under an argon atmosphere at a temperature of 1400–1500 °C for 1–3 h to obtain a blocky initial sintered body. Subsequently, the obtained blocky initial sintered body is crushed and placed in a ball mill jar with ethanol for wet ball milling to obtain a slurry. The slurry is then placed in a vacuum oven and dried at 120 °C for 12 h to obtain a dry powder.

[0008] Step (3): The dried powder is loaded into a graphite mold and placed in a spark plasma sintering furnace. High-pressure sintering is carried out under the protection of argon atmosphere. Sintering conditions: pressure 10MPa~40MPa, temperature 1100℃~1200℃, sintering time 5min~15min. A MAX phase ceramic material with dense structure and high phase purity is obtained, which is resistant to lead and bismuth corrosion.

[0009] Method 2: Step (1): Using Cr powder, Ti powder, Mo powder, W powder, Al powder, and C powder as raw materials, place them in a ball mill jar for ball milling to ensure that the powders of each element are mixed evenly. Intermittent ball milling is used to prevent the powders from sticking together due to excessive temperature.

[0010] Step (2): Load the powder uniformly mixed by ball milling into a graphite mold, place it in a high-temperature tube furnace, and carry out a pressure-applied high-temperature solid-phase reaction under the protection of an argon atmosphere, with a pressurization pressure of 10 MPa to 40 MPa, a reaction temperature of 1400 to 1500°C, and a holding time of 1 to 3 h, to obtain the target MAX-phase corrosion-resistant ceramic material resistant to lead-bismuth corrosion.

[0011] The purities of Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder used in the above two methods are ≥99%. The stoichiometric molar ratio of Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder is preferably 1.75:1.65:0.6 x:x:1.35:3, 0<x≤0.2. Since Al will volatilize at high temperature and react with the graphite mold, it is necessary to add some extra Al powder to avoid Al deficiency.

[0012] Preferably, the first method is adopted to prepare the W-containing multi-element MAX-phase corrosion-resistant ceramic material, and the combination of pressureless high-temperature solid-phase reaction and spark plasma sintering can maximize the density of the ceramic material.

[0013] The W-containing multi-element MAX-phase ceramic material provided by the present invention is used in a liquid lead-bismuth environment at 500°C to 600°C, and can be used as a structural material for lead-cooled fast reactors.

[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses Cr 1.75 Ti 1.65 Mo 0.6 AlC₃ as the matrix, and uses W element to replace the Mo element reduced in an equimolar ratio to prepare a W-doped Cr-Ti-Mo-W multi-element MAX-phase ceramic material. The introduction of W element has a dual-action mechanism: on the one hand, part of W occupies the 4f lattice position, which improves the structural stability of the MC-type carbide layer by enhancing the transition metal-carbon bond strength, and at the same time weakens the bond between the transition metal and the aluminum layer, making it easier to break, thus promoting the selective leaching of Al; on the other hand, the incorporation of W effectively reduces the Gibbs free energy for Al₂O₃ formation, which is conducive to inducing the formation of a dense Al₂O₃ protective layer under oxygen-poor conditions. Benefiting from the above mechanism, the prepared ceramic material exhibits a stability of up to 2000 hours in the lead-bismuth corrosion environment, significantly improving its corrosion resistance.

[0015] (2) Compared with the alloy materials used in existing lead-cooled fast reactors, the mechanical properties of the W-containing multi-element MAX-phase ceramic material of the present invention are improved, with a nanohardness of 11 GPa to 15 GPa, thereby reducing the loss caused by fretting wear and erosion wear during service, and since the matrix material contains Ti element with good ductility, it has little effect on the brittleness of the material.

[0016] (3) The present invention utilizes W doping to enhance the strength of the carbide portion and weaken the elemental bonding of the Al layer, promotes the selective dissolution of Al during the corrosion process, and at the same time reduces the Gibbs free energy when Al2O3 is generated during the corrosion process, so that it can form a continuous oxide layer more quickly and protect the substrate material from corrosion.

[0017] (4) The composition of the W-containing multi-element MAX phase ceramic material of the present invention is easy to control, and the required raw material powder is easy to obtain, all of which are commercially available raw materials; the heat preservation and cooling time during the preparation process is short, and the process is simple.

[0018] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0019] Figure 1 The X-ray diffraction patterns are those of the MAX phase ceramic materials obtained in Comparative Example 1, Example 1, and Example 2. Here, a, b, and c represent the ceramic materials of Comparative Example 1, Example 1, and Example 2, respectively.

[0020] Figure 2 The images show cross-sectional scanning electron microscope (SEM) images and EDS spectra of the MAX phase ceramic materials of Comparative Example 1, Example 1, and Example 2 after corrosion tests in a liquid lead-bismuth environment at 550°C.

[0021] Figure 3 The images show the cross-sectional transmission electron microscope images and EDS line scan elemental distribution maps of the W-containing multi-element MAX phase ceramic material prepared in Example 1 after corrosion testing in a liquid lead-bismuth environment at 550℃ for 2000 h.

[0022] Figure 4 This is a comparison chart showing the solubility of each element in the MAX phase ceramic materials obtained in Comparative Example 1, Example 1, and Example 2 after corrosion testing in a liquid lead-bismuth environment at 550°C.

[0023] Figure 5 The graph shows the Gibbs free energy of the MAX phase ceramic materials obtained in Comparative Example 1, Example 1, and Example 2 as a function of temperature. Detailed Implementation

[0024] The preferred embodiments of the present invention will be described below with reference to the accompanying drawings. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0025] Example 1 A W-containing multi-element MAX phase ceramic material resistant to lead-bismuth corrosion (Cr 1.75 Ti 1.65 Mo 0.5 W0.1 AlC3), the preparation steps are as follows: Step 1: Using commercially available Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder as raw materials, the ingredients are prepared according to the stoichiometric molar ratio of Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder as 1.75:1.65:0.5:0.1:1.35:3.

[0026] Step 2: Place the prepared raw material powder in a ball mill jar and ball mill twice, each time for 30 minutes, with a 30-minute interval, to obtain a mixed powder.

[0027] Step 3: The mixed powder is placed in a glove box under an argon atmosphere and then loaded into a graphite mold. The mold is then placed in a high-temperature tube furnace and sintered under an argon atmosphere at 1450℃ for 3 hours to obtain a block-shaped pre-sintered body. Subsequently, the obtained block-shaped pre-sintered body is crushed and wet-milled with ethanol in a ball mill jar to obtain a slurry. The slurry is then placed in a vacuum oven and dried at 120℃ for 12 hours to obtain a dry powder.

[0028] Step 4: The dried powder is loaded into a graphite mold in a glove box (under argon atmosphere protection), and the loaded mold is placed in a spark plasma sintering furnace for sintering at a temperature of 1200 ℃, a holding time of 15 min, and a pressure of 30 MPa to prepare a W-containing multi-element MAX phase ceramic material.

[0029] Example 2 A W-containing multi-element MAX phase ceramic material resistant to lead-bismuth corrosion (Cr 1.75 Ti 1.65 Mo 0.4 W 0.2 AlC3), the preparation steps are as follows: Step 1: Using commercially available Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder as raw materials, the ingredients are prepared according to the stoichiometric molar ratio of Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder of 1.75:1.65:0.4:0.2:1.35:3.

[0030] Steps 2-4 are the same as in Example 1.

[0031] Comparative Example 1 A multi-element MAX phase ceramic material (Cr 1.75 Ti 1.65 Mo 0.6 AlC3), the preparation steps are as follows: Step 1: Using commercially available Cr powder, Ti powder, Mo powder, Al powder and C powder as raw materials, the ingredients are prepared according to the stoichiometric molar ratio of Cr powder, Ti powder, Mo powder, Al powder and C powder of 1.75:1.65:0.6:1.35:3.

[0032] Steps 2-4 are the same as in Example 1.

[0033] Figure 1 The X-ray diffraction patterns of the MAX phase ceramic materials obtained in Comparative Example 1, Example 1, and Example 2 are shown below. Wherein, a, b, and c represent the ceramic materials of Comparative Example 1, Example 1, and Example 2, respectively. It can be seen that the diffraction peak shapes of the ceramic materials in Comparative Example 1 and the two examples are consistent with the peak shapes of (CrTiMo)4AlC3 obtained through fitting. The purity of the ceramic material obtained in Comparative Example 1 is 91.0%, the purity of the ceramic material obtained in Example 1 is 93.0%, and the purity of the ceramic material obtained in Example 2 is 92.7%. This indicates that the ceramic materials obtained in Examples 1 and 2, as well as Comparative Example 1, all possess good crystallinity and phase purity.

[0034] To further verify the lead-bismuth corrosion resistance of the MAX phase ceramic materials obtained in Comparative Example 1, Example 1, and Example 2, the following operations were performed: The MAX phase ceramic materials obtained in Comparative Example 1, Example 1, and Example 2 were processed into cuboid samples of 8mm × 8mm × 2.5mm by wire cutting. The samples were then polished to 3000# sandpaper, ultrasonically cleaned with ethanol for 30 minutes, and dried in a vacuum drying oven for 12 hours to obtain pretreated samples. The pretreated samples were then subjected to corrosion tests in a 550℃ high-temperature box furnace.

[0035] Figure 2is the cross-sectional scanning electron microscope images and EDS spectra of the MAX phase ceramic materials of Comparative Example 1, Example 1 and Example 2 after the corrosion test in a liquid lead-bismuth environment at 550 °C. Among them, a and b are scanning electron microscope images of the sample of Comparative Example 1 at different magnifications, and the corresponding EDS spectra are below the electron microscope images; c and d are scanning electron microscope images of the sample of Example 1 at different magnifications, and the corresponding EDS spectra are below the electron microscope images; e and f are scanning electron microscope images of the sample of Example 2 at different magnifications, and the corresponding EDS spectra are below the electron microscope images. It can be seen that when W is not doped, the matrix at the interface of Comparative Example 1 can be seen to be completely dissolved at a high magnification, and even detached from the main body. After doping with W, the cross section in Example 1 is smooth, and the matrix at the interface is well preserved, without the phenomenon of pulverization due to dissolution. In addition to Al2O3 existing in the matrix itself detected in the EDS spectrum, no other oxides are observed to be formed, and other elements are also uniformly distributed. In Example 2, the dissolution near the surface of the cross section is intensified, the region about 2 to 3 μm from the surface to the matrix is pulverized due to dissolution, and there is a discontinuous dark gray oxide layer under this region, which the EDS spectrum shows may be an Al-containing oxide. It can be seen from the cross-sectional morphology that when the W content is further increased, the surface dissolution is intensified, and the corrosion resistance of the sample decreases. This indicates that doping an appropriate amount of W element can improve the lead-bismuth corrosion resistance of the material, that is, the range of 0 < x ≤ 0.2 needs to be limited to improve the lead-bismuth corrosion resistance of the ceramic material.

[0036] Figure 3 is the cross-sectional transmission electron microscope (TEM) image of the W-containing multi-element MAX phase ceramic material prepared in Example 1 after 2000 h of corrosion test in a liquid lead-bismuth environment at 550 °C. From Figure 3 the TEM and EDS spectra in the high-angle annular dark field mode of (a), it can be seen that a crack extending from the sample surface deep into the interior of the matrix can be observed in the matrix, and there is a continuous oxide layer with a size of about 20 to 30 nm between the matrix and the lead-bismuth residue, and the phase composition of the oxide layer is mainly Al2O3. Figure 3 (b) is the EDS line scan element distribution map at the corrosion interface, and it can be observed that Al and O elements are enriched along the direction of cracks and grain boundaries, which indicates that the Al element in the matrix may migrate to the sample surface through this path to form the corresponding oxide, forming a protective oxide layer.

[0037] Figure 4 and Table 1 show the dissolution rates of each element of the MAX phase ceramic materials of Comparative Example 1, Example 1 and Example 2 after the corrosion test in a liquid lead-bismuth environment at 550 °C.

[0038] Table 1 Dissolution rate of each element in W-containing multi-element MAX phase ceramic materials

[0039] Note: "-" indicates no data.

[0040] As shown in Table 1 and Figure 4 As shown, after normalization, the molar solubility of Cr, Ti, Mo, and Al in Comparative Example 1 were 0.009%, 0.025%, 0.008%, and 0.26%, respectively. When an appropriate amount of W was doped, the molar solubility of Cr, Ti, Mo, W, and Al in Example 1 were 0.005%, 0.005%, 0.006%, 0.002%, and 0.0719%, respectively. When the W doping was larger, the molar solubility of Cr, Ti, Mo, W, and Al in Example 2 were 0.008%, 0.031%, 0.019%, 0.006%, and 0.261%, respectively. Except for Al, the solubility of the other elements in Example 1 was not significantly different from that in Comparative Example 1 and Example 2, while the solubility of Al was significantly lower than that in Comparative Example 1 and Example 2. This indicates that appropriate W doping can prevent the loss of Al during the corrosion process.

[0041] Figure 5 The graph shows the Gibbs free energy of the ceramic materials in Comparative Example 1, Example 1, and Example 2 as a function of temperature. At a temperature of 823.15 K (550 °C), the ceramic material in Example 1 has the lowest Gibbs free energy required to generate Al2O3. This indicates that appropriate W doping reduces the energy required to generate Al2O3, promotes the migration of Al during the corrosion process, and is beneficial for inducing the formation of a dense Al2O3 protective layer under oxygen-deficient conditions.

[0042] This invention employs a 413-phase MAX phase matrix, selecting W to partially replace Mo to obtain a specific MAX phase ceramic material resistant to lead-bismuth corrosion. The MAX phase matrix of this invention belongs to a completely different system from the existing 211-phase MAX phase matrix. Related studies have shown that elemental combinations that can exist in the 211 system are not applicable to the 413 system (for example, Cr2AlC has no corresponding Cr4AlC3 phase). The research in this invention found that in the 413 system, elements such as W, Nb, and Ta cannot form thermodynamically stable MAX phase products with Cr or Ti alone; only in the presence of Mo, and only when W replaces an appropriate amount of Mo, can a significant improvement in resistance to lead-bismuth corrosion be achieved; moreover, the technical approach of this invention is not applicable to the 211-phase MAX phase matrix. In the 413 system of this invention, the partial substitution of Mo by W can reduce the interlayer M-Al bond strength, promoting the migration of Al elements during corrosion; simultaneously, W reduces the energy required to form corrosion-resistant Al2O3, which is beneficial for inducing the formation of a dense Al2O3 protective layer under oxygen-deficient conditions. However, similar technical effects cannot be produced in the 211-phase MAX phase matrix.

[0043] In summary, this invention, based on a 413-phase MAX phase matrix, yields a W-containing multi-element MAX phase ceramic material resistant to lead-bismuth corrosion. This ceramic material exhibits excellent corrosion resistance in a liquid lead-bismuth environment. Furthermore, the preparation method is simple, quick, and yields a dense material with high phase purity and good resistance to lead-bismuth corrosion, effectively solving the corrosion and dissolution problem of materials in high-temperature liquid metal environments.

[0044] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A W-containing multi-element MAX phase ceramic material resistant to lead-bismuth corrosion, characterized in that, This ceramic material uses Cr 1.75 Ti 1.65 Mo 0.6 The material was prepared by partially substituting Mo with W as a matrix, and its chemical formula is as follows: Cr 1.75 Ti 1.65 Mo 0.6 x W x AlC3, where 0 <x≤0.2。 2. The lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material as described in claim 1, characterized in that, This ceramic material is prepared by ball milling and mixing Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder, followed by high-temperature solid-phase reaction under argon atmosphere protection, and then spark plasma sintering treatment.

3. The lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material as described in claim 2, characterized in that, The conditions for the high-temperature solid-state reaction are: reaction temperature of 1400-1500℃, holding time of 1-3h, to obtain a blocky initial sintered body.

4. The lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material as described in claim 3, characterized in that, The blocky initial sintered body is dried after wet ball milling to obtain a dry powder.

5. The lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material as described in claim 4, characterized in that, The dried powder is subjected to spark plasma sintering treatment under the following conditions: temperature of 1100℃~1200℃, time of 5min~15min, and pressure of 10MPa~40MPa.

6. The lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material as described in claim 1, characterized in that, This ceramic material is prepared by ball milling and mixing Cr powder, Ti powder, Mo powder, W powder, Al powder and C powder, followed by a high-temperature solid-state reaction under pressure under argon atmosphere protection.

7. The lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material as described in claim 6, characterized in that, The conditions for the pressurized high-temperature solid-phase reaction are: pressurization pressure of 10MPa to 40MPa, reaction temperature of 1400 to 1500℃, and holding time of 1 to 3h.

8. The application of a lead-bismuth corrosion-resistant W-containing multi-element MAX phase ceramic material as described in any one of claims 1-7, characterized in that, Used as a structural material in lead-cooled fast reactors.